The role of matrix effects on the quantification of abscisic acid and its metabolites in the leaves of Bauhinia variegata L. using liquid chromatography combined with tandem mass spectrometry - Silva, Carolina M. Santiago da [UNESP]; Habermann, Gustavo [UNESP]; Marchi, Mary Rosa Rodrigues de [UNESP]; Zocolo, Guilherme J. [UNESP] (Brazilian Journal of Plant Physiology, 2012)
Phytohormone analysis using liquid chromatography combined with tandem mass spectrometry is a very important tool for studies involving plant metabolism; however, this analysis can be affected by matrix composition. Although it is necessary to understand this effect to produce reliable results, it has been widely neglected in analyses of plant hormones. Leaf extracts from Bauhinia variegata were obtained by solvent extraction followed by solid-phase cleanup. The extract was analyzed with liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) in negative ionization mode, using the multiple reaction monitoring mode with two or three transitions to enhance analytical quality control. Although deuterated standards were used as surrogates, pronounced matrix effects were detected for phaseic acid (PA), abscisic acid (ABA) -glycosyl ester (ABA-GE) and dihydrophaseic acid (DPA), whereas ABA, neoPA and 7'-hydroxy-ABA (7'OHABA) showed negligible matrix effects. The method was validated using spiked samples and was applied to monitor ABA, PA, DPA, neoPA, 7Â´OHABA and ABA-GE on a daily basis. Analyte recoveries from spiked samples ranged from 67% to 87%. The highest leaf concentration of phytohormones was found at 2:00 pm and 5:00 pm, which represent typical day times related to the decrease of stomatal conductance. Despite the use of deuterated phytohormones as internal standards, we showed that the use of a calibration curve constructed with a matrix extract is mandatory for the reliable quantification of ABA and its metabolites, especially PA, ABA-GE and DPA. Daily variations in endogenous ABA leaf concentration were discussed.
Keywords: ABA-β-D-glucosyl ester; ABA daily variations; dihydrophaseic acid; LC-ESI-MS/MS; phaseic acid